ChemInform Abstract: The Palladium‐Catalyzed anti‐Markovnikov Hydroalkylation of Allylic Alcohol Derivatives. Issue 20 (25th April 2013) - DeLuca, Ryan J.; Sigman, Matthew S.
Abstract Allylic, homoallylic, and bishomoallylic protected alcohols react with alkyl zinc reagents to afford the anti‐Markovnikov products exclusively.